2021
DOI: 10.1111/jvh.13607
|View full text |Cite
|
Sign up to set email alerts
|

Viral and bacterial factors of mother‐to‐child transmission of hepatitis B virus

Abstract: Hepatitis B virus (HBV) infection is the tenth leading cause of death worldwide. Mother‐to‐child transmission of HBV occurring mainly at delivery remains one of the most common routes of infection in developing countries. One of the main challenges concerning HBV in Africa is to implement a prevention policy aiming at interrupting the cycle of pseudo‐vertical transmission of this infection. The aim of this study was to assess the implication of certain bacterial and viral factors in mother‐to‐child transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Another study indicated that nearly 30% of women believe that CS is the safest delivery option for the foetus [ 8 ]. It has been previously reported that most mothers believe CS is safer than natural delivery, takes less time, and reduces the risk of HBV transmission during birth [ 10 ]. These beliefs and opinions are assumed to directly influence the choice of the delivery mode.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that nearly 30% of women believe that CS is the safest delivery option for the foetus [ 8 ]. It has been previously reported that most mothers believe CS is safer than natural delivery, takes less time, and reduces the risk of HBV transmission during birth [ 10 ]. These beliefs and opinions are assumed to directly influence the choice of the delivery mode.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that nearly 30% of women believe that a CS is the safest option for the fetus [8]. We previously reported that most mothers believe that CS is safer than natural delivery, shortens the time of delivery, and reduces the risk of neonatal HBV infection during vaginal birth [10]. These beliefs and opinions are considered to directly in uence the mode of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the numbers of Lactobacillus in the vagina of pregnant women was negatively correlated with the concentration of pro-in ammatory factors interleukin (IL)-6 and IL-8 [21]. Concurrently, some studies have shown a higher detection rate of HBV DNA in the vagina of patients with active HBV replication than that of the general population [10], and the concentration of IL-6 and IL-8 was also found to be higher than that of the non-HBV infected population [22,23]. Therefore, we hypothesize that active HBV replication may interfere with the normal vaginal environment of pregnant women through pro-in ammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection is a global health problem 1–3 . Vertical transmission of HBV from hepatitis B surface antigen (HBsAg)‐positive mothers to their neonates is the most common cause of HBV infection worldwide 4–6 . Despite passive–active immunoprophylaxis using hepatitis B vaccination with or without hepatitis B immunoglobulin, up to 8%–10% of newborns still acquire HBV infection 7 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Vertical transmission of HBV from hepatitis B surface antigen (HBsAg)-positive mothers to their neonates is the most common cause of HBV infection worldwide. [4][5][6] Despite passive-active immunoprophylaxis using hepatitis B vaccination with or without hepatitis B immunoglobulin, up to 8%-10% of newborns still acquire HBV infection. 7 Managing these children with HBV infection is of paramount importance, which has a direct and significant impact…”
mentioning
confidence: 99%